2014
DOI: 10.1007/s00335-014-9537-8
|View full text |Cite
|
Sign up to set email alerts
|

A high resolution map of mammalian X chromosome fragile regions assessed by large-scale comparative genomics

Abstract: Chromosomal evolution involves multiple changes at structural and numerical levels. These changes, which are related to the variation of the gene number and their location, can be tracked by the identification of syntenic blocks (SB). First reports proposed that ~180-280 SB might be shared by mouse and human species. More recently, further studies including additional genomes have identified up to ~1,400 SB during the evolution of eutherian species. A considerable number of studies regarding the X chromosome's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 112 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…We found that nine NPD genes are located inside or adjacent to fragile regions previously reported in the human X chromosome [23], with 28 NPD genes found to be less conserved among primates (<90% identity) and with 5 NPD genes showing a unique gene structure in humans, compared with orthologues.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We found that nine NPD genes are located inside or adjacent to fragile regions previously reported in the human X chromosome [23], with 28 NPD genes found to be less conserved among primates (<90% identity) and with 5 NPD genes showing a unique gene structure in humans, compared with orthologues.…”
Section: Discussionmentioning
confidence: 82%
“…Genes that have a unique gene structure in humans, compared with orthologues, were identified. Additionally, NPD genes that are located near or inside fragile regions of human X chromosome were recognized [23]. …”
Section: Methodsmentioning
confidence: 99%
“…The onset of bioinformatic methods and databases in recent years provides the potential to simultaneously identify many regions prone to fragility, making them strong candidates for further analysis. Prada and Laissue (2014) used bioinformatic methods to identify chromosomal rearrangements of the X chromosome in 13 different mammalian species ( Prada and Laissue, 2014 ). They identified fragile sites previously associated with the human X chromosome (FRAXA, B, C, D, E, and F), and were also able to determine fragile sites that are conserved between mammalian species, implying that these regions could have functional roles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, innovative diagnostic approaches have been proposed for pathologies having overlapping phenotypes and which are caused by various genes [ 43 , 44 ]. The available data regarding the genomes of particular mammalian species has enabled large-scale comparative genomics approaches leading to dissecting loci related to evolution mechanisms and potentially contributing towards human diseases [ 51 ]. Moreover, complex pathologies such as female infertility have also been explored via NGS (Fonseca et al in press).…”
Section: Introductionmentioning
confidence: 99%